Management of temporomandibular disorders and occlusion - Okeson , Jeffey P. (St. Louis, Estados Unidos de America : Mosby, 1985)
Parte I -- Funtional anatomy and biomechanics of the masticatory system -- Functional Neuroanatomy and phisiology of the masticatory system -- Alignment and occlusion of the dentition -- Mechanics of mandibular movement -- Criteria for optimun funtional occlusion -- Determinants of occlusal morphology -- Parte I: Etilogy and identification of funtional disturbances in the masticatory system -- Etiology of funtional disturbances in the masticatory system -- Signs and symphoms of of temporomandibular disorders --History and examination for temporomandibular disorders -- Diagnosis of temporomandibular disorders -- Parte III Treatment of funtional disturbances of the masticatory system -- General considerations in the treatment of temporomandibular disorders -- Treatment of masticatory muscle disorders -- Treatment of temporomandibular joint disorders -- Treatment of chronic hypomobility and growth disorders -- occlusal appliance therapy -- Treatment ofsequencing -- Parte IV: occlusal therapy -- General considerations in occlusal therapy -- Use of aticulators in occlusal therapy -- Selective grinding -- Restorative consideretions in occlusal therapy.
Incluye foreword -- Prefacio
References: 60-63, 125-126, 221-227, 296-301, 339-341
Keywords: Oclusion dental; Maloclusion